Smoking in athletes with asthma - Todaro, A.; Appodia, M.; Di Cave, P. (Medicina dello Sport, 2015)
Aim. Many athletes smoke tobacco and many athletes suffer from asthma; however, data is scant on smoking in athletes with asthma. The aim of this study was to identify in a sample of athletes with diagnosed bronchial asthma those who also smoked and to determine the effects of smoking on respiratory function.